Analysis of Human Resource Management Strategies in Improving Organizational Performance - Junaidi, Muhammad; Partayasa, Ketut; Sulaimawan, Deddy (Universitas Bumigora, 2024)
Human Resource Management (HRM) has been recognized as a key element in achieving competitive advantage and sustainable organizational performance. In a dynamic and rapidly changing business environment, organizations need to develop effective HRM strategies to utilize the full potential of their human resources. This research aims to determine effective HRM strategies in improving organizational performance, with a focus on tapioca flour industry companies in the East Camping region. The case study research method was used to obtain an in-depth understanding of the implementation of HRM strategies in organizations. The sample used was 63 respondents from various positions and roles. The analysis uses a qualitative approach. The contribution of this study lies in proving the importance of strategic human resource practices such as adept recruitment and selection processes, comprehensive employee development initiatives, and sustainable performance management systems. These elements play a pivotal role in enhancing organizational performance. Therefore, companies are encouraged to delve deeper into integrating new technologies into HRM practices to leverage their potential benefits in the evolving digital landscape. The research underscores that organizations which implement robust human resource strategies tend to achieve superior performance outcomes in contemporary business environments. Such strategies play a crucial role in ensuring competitive advantage and sustained success in today's dynamic market landscape.